The Ghost of St Stephen's or The Stranger at Home! - Woodward, G. M. (George Moutard), ca. 1760-1809 (Hixon, 1800)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Ireland -- History -- Union, 1801